2017
DOI: 10.1002/phar.1946
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Drug Dosing in Gilbert Syndrome Associated with UGT1A1: A Summary of the Literature

Abstract: Gilbert syndrome (GS) is a hereditary condition that affects ~10% of the population. It is characterized by intermittent, unconjugated hyperbilirubinemia in the absence of hepatocellular damage and hemolysis. Although GS is often described as a benign laboratory finding, it may alter drug metabolism by decreasing the ability to conjugate drugs. Genetic polymorphisms, specifically the UGT1A1*28 allele, may reduce glucuronidation by 30% that severely impacts the ability to metabolize certain medications. Antineo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…Наиболее хорошо охарактеризованы аллель *28, представляющий собой амплификацию динуклиотидных повторов ТА в промоторе, и аллель *6 SNP, приводящий к значимой аминокислотной замене (Gly71Arg). Особо выделяют гомозиготное состояние аллеля *28, которое является основной причиной развития наследственного синдрома Жильбера [9]. В случае химиотерапии иринотеканом у носителей упомянутых полиморфизмов чрезмерно накапливается активный метаболит (SN-38) и развиваются тяжелые токсические реакции.…”
Section: Introductionunclassified
“…Наиболее хорошо охарактеризованы аллель *28, представляющий собой амплификацию динуклиотидных повторов ТА в промоторе, и аллель *6 SNP, приводящий к значимой аминокислотной замене (Gly71Arg). Особо выделяют гомозиготное состояние аллеля *28, которое является основной причиной развития наследственного синдрома Жильбера [9]. В случае химиотерапии иринотеканом у носителей упомянутых полиморфизмов чрезмерно накапливается активный метаболит (SN-38) и развиваются тяжелые токсические реакции.…”
Section: Introductionunclassified
“…The presence of seven or eight TA repeats in the promoter of the UGT1A1 gene could severely impact the ability to metabolize certain medications, including antineoplastic drugs used in oncology: irinotecan (solid tumors, lymphoma and colorectal cancer treatment), belinostat (peripheral T-cell lymphoma treatment), epirubicin (breast cancer treatment), 5-fluorouracil (colorectal cancer treatment), axitinib and busulfan (various hematological and non hematological cancers), atazanavir and ritonavir (HIV infections treatment) and widely used analgesic/antipyretic drug acetaminophen (paracetamol). Alterations in hepatic metabolism may result in life-threatening toxicities in various organ systems [ 17 , 18 ]. Recommendations for pharmacogenomic testing for several of these drugs are given and have already been applied in routine clinical practice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acetaminophen (~85%) is metabolized by conjugation, mainly glucuronidation through UDP-glucuro nosyltransferase (33). Ha et al (10) revealed that UGT1A1 genetic polymorphisms, particularly the UGT1A1 * 28 allele of GS may alter the metabolism of drugs, such as irinotecan hydrochloride by decreasing the ability to conjugate drugs. Attention should be paid to the use of these drugs in patients with GS.…”
Section: Discussionmentioning
confidence: 99%
“…GS in combination with diseases, such as thalassemia, glucose-6 -phosphate dehydrogenase (G6PD) deficiency, spherocytosis and acute lymphoblastic leukemia may potentiate severe hyperbilirubinemia (5)(6)(7)(8)(9). In addition, GS may decrease plasma oxidation and affect drug metabolism, such as irinotecan hydrochloride by decreasing the ability to conjugate drugs (10). However, to the best of our knowledge, there are currently no reports about patients with systemic lupus erythematosus (SLE) coexisting with GS.…”
Section: Introductionmentioning
confidence: 99%